First Clinical Isolation of an Azole-Resistant Aspergillus fumigatus Isolate Harboring a TR46 Y121F T289A Mutation in South America - Isla, Guillermina (2018)
Fil: Isla, Guillermina. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas. Departamento de Micología; Argentina.